Theoretical predictions of aromatic Be–O rings. Issue 36 (21st August 2018) - Dutton, Jason L.; Wilson, David J. D.
Abstract : We have carried out a theoretical investigation of benzene substituted with BeO to assess stability and aromatic properties (with 1–3 BeO units in a six-membered ring); C4 H4 BeO, C2 H2 Be2 O2, and Be3 O3 . Abstract : We have carried out a theoretical investigation of benzene substituted with BeO to assess stability and aromatic properties (with 1–3 BeO units in a six-membered ring); C4 H4 BeO, C2 H2 Be2 O2, and Be3 O3 . All species retain a planar geometry. We considered both bare complexes and Be coordinated with L = CO, pyridine, PMe3, and NHC. Coordination of a ligand to Be atoms causes increased Be–O bond distances. Aromatic character has been investigated with NICS and NICS-scan calculations, EDA analysis, as well as considering the energetics of hydrogenation. The complexes with the greatest aromatic character are C4 H4 BeO (3 ), and C4 H4 Be(CO), which have negative NICS(1) zz values and minima in the NICS-scan. Coordination of two ligands to make the Be four-coordinate disrupts ring planarity and reduces aromatic character.